Influence Of Tooth Designs On Electromagnetic Characteristics In Fractional-Slot Permanent Magnet Brushless Machine - Zolkapli, Zulfikri Zaki (2016)
Due to factors such as a simpler construction and high torque density, the Permanent Magnet (PM) electric machines are favorable as an alternative to other conventional machine topologies. However, the PM machines may result high torque ripple due to the influences of cogging torque and electronic commutation respectively. In this research, an influence of various stator tooth designs on the electromagnetic characteristics in Fractional-Slot PM machines is investigated using 2D Finite-Element Analysis software, Ansys Maxwell. The influences of having additional thin PM on stator tooth-tip, asymmetric design of stator tooth-tip and the notch numbers and notch dimension are investigated for the purpose of torque ripple reduction at rated condition without degrading the average torque. By introducing these factors, the existing flux flows along the stator iron path would be affected leading to a potential change on the machine’s electromagnetic characteristics. The research has focused into the twelve-slot/ten-pole motor equipped with alternate tooth winding as it results more trapezoidal back-emf and lesser torque ripple. From the investigation, it is confirmed that a reduction of high torque ripple leading to a more constant torque at rated condition is desirable. It is also found that the machine which stator is modified has a significant reduction of torque ripple at about thirty-nine percent. For a verification purpose, the prototype motor design which is based on the lowest output torque ripple is developed and tested. A good agreement between predicted and measured results is achieved. The prototype design is then proposed for the application of robotic system.